The Best Damn Cisco Internetworking Book Period - Riley, Charles (Syngress Publishing, 2011)
The Best Damn Cisco Internetworking Book Period shows readers everything they need to know about all Cisco internetworking topics. The book provides an understanding of Cisco's current VoIP solutions and the means to put them to work, showing how to configure all of Cisco's core VoIP products-among them Cisco CallManager software, Cisco 7910 series phones, and server-based IP PBXs. It discusses IPv6 Protocols, as well as IP Quality of Service (QoS) and how it applies to Enterprise and Internet Service Provider (ISP) environments. In addition, Cisco wireless technologies are covered in detail. Cisco has placed a high priority on security and here readers will find complete coverage of all the Cisco Security products such as the PIX firewall suite of products, Network Address Translation (NAT), Cisco VPN Concentrator and IPSec, Cisco Authentication, Authorization, and Accounting (AAA), Content Services Switch (CSS), and the Cisco Secure Network Intrusion Detection System.